Soluble Non-Starch Polysaccharides From Plantain (Musa x paradisiaca L.) Diminish Epithelial Impact of Clostridioides difficile - Simpson, Hannah L.; Roberts, Carol L.; Thompson, Louise M.; Leiper, Cameron R.; Gittens, Nehana; Trotter, Ellie; Duckworth, Carrie A.; Papoutsopoulou, Stamatia; Miyajima, Fabio; Roberts, Paul; O’Kennedy, Niamh; Rhodes, Jonathan M.; et al. (Frontiers in Pharmacology, 2021)
Clostridioides difficile infection (CDI) is a leading cause of antibiotic-associated diarrhoea. Adhesion of this Gram-positive pathogen to the intestinal epithelium is a crucial step in CDI, with recurrence and relapse of disease dependent on epithelial interaction of its endospores. Close proximity, or adhesion of, hypervirulent strains to the intestinal mucosa are also likely to be necessary for the release of C. difficile toxins, which when internalized, result in intestinal epithelial cell rounding, damage, inflammation, loss of barrier function and diarrhoea. Interrupting these C. difficile-epithelium interactions could therefore represent a promising therapeutic strategy to prevent and treat CDI. Intake of dietary fibre is widely recognised as being beneficial for intestinal health, and we have previously shown that soluble non-starch polysaccharides (NSP) from plantain banana (Musa spp.), can block epithelial adhesion and invasion of a number of gut pathogens, such as E. coli and Salmonellae. Here, we assessed the action of plantain NSP, and a range of alternative soluble plant fibres, for inhibitory action on epithelial interactions of C. difficile clinical isolates, purified endospore preparations and toxins. We found that plantain NSP possessed ability to disrupt epithelial adhesion of C. difficile vegetative cells and spores, with inhibitory activity against C. difficile found within the acidic (pectin-rich) polysaccharide component, through interaction with the intestinal epithelium. Similar activity was found with NSP purified from broccoli and leek, although seen to be less potent than NSP from plantain. Whilst plantain NSP could not block the interaction and intracellular action of purified C. difficile toxins, it significantly diminished the epithelial impact of C. difficile, reducing both bacteria and toxin induced inflammation, activation of caspase 3/7 and cytotoxicity in human intestinal cell-line and murine intestinal organoid cultures. Dietary supplementation with soluble NSP from plantain may therefore confer a protective effect in CDI patients by preventing adhesion of C. difficile to the mucosa, i.e. a ‘contrabiotic’ effect, and diminishing its epithelial impact. This suggests that plantain soluble dietary fibre may be a therapeutically effective nutritional product for use in the prevention or treatment of CDI and antibiotic-associated diarrhoea.